Scapegoats : transferring blame - Douglas, Tom (Routledge, 1995)
Scapegoats are a universal phenomenon, appearing in all societies at all times in groups large and small, in public and private organizations. Hardly a week passes without some media reference to someone or something being made a scapegoat. Tom Douglas examines the process of scapegoating from the perspectives of victims and perpetrators, tracing its development from earliest times as rite of atonement to the modern forms of the avoidance of blame and the victimisation of innocents. The differences and similarities between the ancient and modern forms are examined to reveal that despite the mo.